Pengaruh temperatur terhadap struktur mikro dan sifat mekanik dalam proses fussion brazing Ni-Hard 4 dengan S45C menggunakan CuZn 35 sebagai logam pengisi. - Siswanto, Ari; Purwadi, W. (Universitas Mataram, 2020)
This research was conducted on white cast iron (Ni-Hard 4) and medium carbon steel (S45C) cast iron materials using a thin brass plate (CuZn 35) 0.3 mm as filler metal by heating at temperatures of 850 to 1050 0C for 120 minutes with a pressure of 2 Mpa in the muffle furnace. The effect of temperature on the microstructure was observed using an optical microscope and scanning electron microscopy equipped with energy dispersive X-ray system (EDS) to determine the chemical composition that occurred between the three meterial layers. The thickness of the interface layer increases with increasing holding temperature. The highest shear strength (79.86 Mpa) was obtained at a temperature of 950 0C.